TEACHING COMMUNITY INTERPRETING IN UKRAINE - Povoroznyuk, Roksolana; Kolodii, Bogdana (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article deals with a specific type of interpreting which gained prominence among the scholars during the recent decades. Community interpreting is found more in community-based than organizational situations. It is a particularly vital service in communities with large numbers of ethnic minorities and foreigners, enabling those representatives to access services where, due to the language barrier, they would otherwise find it difficult. Situations where such interpreters are necessary typically include medical, educational, housing, social security and legal areas. Community interpreting is described in relation to its core teaching aspects (context, mode and medium-bound ones). The authors offer their insight into the national specifics of teaching and performing community interpreting in Ukraine. For this purpose, the interpreting and translation curriculum of the Institute of Philology by Taras Shevchenko National University of Kyiv was taken as the benchmark. Attention is riveted to the reflection on the unequal distribution of community interpreting-oriented courses in the University curriculum. The authors also outline the training methodology for the community interpreting competence and skills. Aim. The aim of this paper is to ascertain the CI status as an independent discipline within the framework of the Ukrainian higher education, reveal the national specifics of CI services delivery in Ukraine reflecting on the unequal distribution of CI-related courses in the University curriculum, and outline the training methodology for the CI competence and skills. Methodology. This research is a mixed-method qualitative study based on the analysis of the interpreting and translation curriculum of the Institute of Philology by Taras Shevchenko National University of Kyiv. Quantitative methods were used to illustrate our theoretical findings wherever applicable. An attempted contrastive description delineates the current CI teaching status in Ukraine and other countries where CI is viewed as an independent course; professional certification and licensing are equally provided. Results. Effective teaching CI at the higher educational institutions presupposes a multi-task attention-sharing activity, as it has context-, medium-, and mode-bound aspects, which should find their equal representation in the curriculum. Moreover, every aspect comes with its own set of KSAs (Knowledge, Skills, and Abilities) to be further integrated into the teaching process. Value/Originality. Continued (temporary and permanent) migrant flow, multilingualism and cultural plurality demand the imminent emergence of CI profession in Ukraine as a need for a bridge between a mainstream culture served by the official language and various ethnic groups is acutely felt nowadays; thus raising an issue of professional training and accreditation which has never been properly addressed. Studies of interpreter-mediated activities in Ukraine are absent as well precluding any possible estimations of their quality. An important cultural outcropping of CI development is a possibility of healing an ontological chasm which exists between the Russian and Ukrainian-speaking residents of various Ukrainian regions. Conclusions. CI training flourishes through a collaboration of the national educational establishments with their EU, British and US counterparts, engaging in a collective CI syllabus creation, implementing an independent CI specialization (major), in tune with the emerging national aspirations to become wholly integrated, human right advocating and culturally cognizant global players. ______________ References • Anderson, R., & Bruce, W. (1978). Interpreter Roles and Interpretation Situations: CrossCutting Typologies. In D. Gerver, H. & W. Sinaiko (Eds.), Interpreter Roles and Interpretation Situations: CrossCutting Typologie, 217–229. doi: 1007/978-1-4615-9077-4_20. • Angelelli, C. (2004). Medical interpreting and cross-cultural communication. New York: Cambridge University Press. • Angelelli, C. (2017). Anchoring Dialogue Interpreting in Principles of Teaching and Learning. In L. Cirillo, & N. Niemants (Eds.), Teaching Dialogue Interpreting: Research-based proposals for higher education. Amsterdam: John Benjamins Publishing Company, 29–44. doi:1075/btl.138. • Braun, S., & Taylor, J. (2012). Video-mediated interpreting in criminal proceedings: Two European surveys. In S. Braun & J. Taylor (Eds.), Videoconference and Remote Interpreting in Criminal Proceedings (pp. 69–98). Cambridge/Antwerp: Intersentia. • Cirillo, L., & Niemants, N. (2017). Dialogue interpreting: Research, education and professional practice. In L. Cirillo & N. Niemants (Eds.), Teaching Dialogue Interpreting: Research-based proposals for higher education. Amsterdam: John Benjamins Publishing Company, 2–25. doi:10.1075/btl.138. • Cirillo, L., & Radicioni, M. (2017). (Role-)playing Fair(s). In L. Cirillo & N. Niemants (Eds.), Teaching Dialogue Interpreting: Research-based proposals for higher education. Amsterdam: John Benjamins Publishing Company, 119–136. doi:1075/btl.138. • Hale, S. et al. (Eds.) (2009). Quality in Interpreting – a Shared Responsibility. Amsterdam: John Benjamins. • Harris, B., & Sherwood, B. (1978). Translating as an Innate Skill. In D. Gerver & H. W. Sinaiko (Eds), Interpreter Roles and Interpretation Situations: CrossCutting Typologies, 155–170. doi:1007/978-1-4615-9077-4_20. • Hrehovčík, T. (2009). Teaching Community Interpreting: A New Challenge? In Milan Ferenčík and Jurag Horváth (Eds), Language, literature and culture in a changing transatlantic world: International conference proceeding (April 22-23, 2009) Prešov: Prešovská Univerzita (pp. 160-164). Retrieved from http://www.pulib.sk/elpub2/FF/Ferencik2/pdf_doc/21.pdf. • Krystallidou, D. (2017). Non-verbals in Dialogue Interpreter Education: Improving Student Interpreter’s Visual Literacy and Raising Awareness of Its Impact on Interpreting Performance. In L. Cirillo & N. Niemants (Eds.), Teaching Dialogue Interpreting: Research-based proposals for higher education. Amsterdam: John Benjamins Publishing Company, 259–274. doi:1075/btl.138. • Krysztofowicz, D., & Krupienicz, Z. (2016). Community interpreting in Poland. Formal legislation, role and opportunities. International Journal of Language, Translation and Intercultural Communication, 5, 84–93. doi: http://dx.doi.org/10.12681/ijltic.10657. • Lee, J. (2009). When linguistic and cultural differences are not disclosed in court interpreting. Multilingua, 28(4), 379-402. doi: https://doi.org/10.1515/mult.2009.017. • Mason, I. (Ed.) (2001). Triadic Exchanges. Studies in Dialogue Interpreting. Manchester, UK: St. Jerome. • Mason, I. (2009). Dialogue interpreting. In M. Baker, & G. Saldanha (Eds.), Routledge Encyclopedia of Translation Studies. 2nd edn. (pp. 81–84) London/New York: Routledge. • Mikkelson, H. (2014). Evolution of public service interpreter training in the U.S. FITISPos International Journal. 1. • Mukhametshina, E., Latypov, N., & Timerkhanov, A. (2018). Teaching community interpreting at university: a challenge of the multicultural society. INTED2018 Proceedings (March 5-7, 2018) Valencia: 6683-6686. • National Council on Interpreting in Health Care (2011). National Standards for Healthcare Interpreter Training Programs. Retrieved from http://www.ncihc.org/assets/documents/publications/ National_Standards_5-09-11.pdf. • Ozolins, U. (2011). Telephone interpreting: Understanding practice and identifying research needs. Translation & Interpreting 3 (2), 33–47. • Pöchhacker, F. (2006). “Going social?” On pathways and paradigms in interpreting studies. In A. Pym, M. Shlesinger & Z. Jettmarová (Eds), Sociocultural Aspects of Translating and Interpreting (pp. 215–232). Amsterdam: John Benjamins. • Pym, A., Fallada, C, Biau, J. R., & Orenstein J. (Eds.) (2003). Innovation and E-Learning in Translator Training. Intercultural Studies Group. Universitat Rovira i Virgili 2003. Retrieved from http://isg.urv.es/publicity/isg/publications/innovation_2003/index.htm. • Roberts, R. (2002). Community interpreting: A profession in search of its identity. In E. Hung (Ed.), Teaching Translation and Interpreting 4: Building Bridges. Amsterdam and Philadelphia: John Benjamins Publishing Company. • Schjoldager, A. (2008). Understanding Translation. Denmark: Academica. • Taibi, M., & Ozolins, U. (2016). Community Translation. London, New York: Bloomsbury Academic, Bloomsbury Advances in interpreting Series. • Takimoto, M. (2006). Interpreters’ role perceptions in business dialogue interpreting situations. Monash university linguistics papers, 5(1), 47-57. • Tiayon, Ch. (2005). Community Interpreting: An African Perspective. In Hermeneus, Revista de Traducción e Interpretación. Espana: Valladolid. No. 7. • Valero-Garcés, C. (2011). Design, Implementation and Evaluation of a Programme on Intercultural Communication and Public Service Interpreting and Translation. In Kainz, Prunč and Schögler (Eds), Modelling the Field of Community Interpreting: questions of methodology in research and training (pp. 125–151). Vienna, Berlin: Verlag. • Wadensjö, C. (1993). Dialogue Interpreting and Shared Knowledge. In Y. Gambier & J. Tommola (Eds.), Dialogue Interpreting and Shared Knowledge (pp. 101-113). Turku: Centre for Translation and Interpreting, University of Turku. • Wadensjö, (1998). Interpreting as Interaction. London and New York: Longman. • Wagner, J. (1995). What Makes a Discourse a Negotiation? In E. Konrad & Wagner J. (Eds.), The Discourse of Business Negotiation (pp. 9-36). Berlin, New York: Mouton de Gruyter.